Heroic Figures’ Characters in Wayang Wong Dance Drama: A Character Education For The Elementary School Students? - Farida Nuryantiningsih; Sri Nani Hari Yanti (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
Wayang Wong is one Javanese traditional dance drama combining drama arts and wayang performance. The stories in Wayang wong performances are taken from Mahabarata and Ramayana. Many stories presented through wayang wong performances give various life examples through each figure’s characters. Of those contained in wayang wong performances, this article only selected the figures from Mahabarata story as not only well known by the society like Gatotkaca, Arjuna, Bima/Werkudara, or Kresna, but also many Mahabarata story figures have good characters appropriate to become the examples for the character education at schools. Love, forgiveness, patience. responsibility, helpfulness, and other good characters belong to the Mahabarata story protagonist figures. This descriptive qualitative research used a cultural approach by identifying wayang wong figures’ characters in both Ramayana and Mahabharata stories. The research data were collected using literature reviews on various relevant references to wayang wong to dig and obtain the descriptions of the wayang wong figures’ characters in both Mahabharata and Ramayana stories as the character education for elementary school students. This article is greatly interesting because by introducing the protagonist figures through wayang wong performances, the children from Javanese ethnicity are expected to have good characters sourced from the local cultures. This is important because by knowing wayang figures, children are taught to love and conserve their nation’s cultures.